Avaliação técnico-econômica da produção de metanol a baixas temperaturas pela oxidação parcial do metano - Sumikawa, Victor Iwao Oliveira (2022)
Large volumes of natural gas (NG) are released or flared on oil platforms, emitting mainly methane, carbon monoxide, and carbon dioxide. These greenhouse gases (GHG) represent an environmental and health hazard. In this context, it is of great interest that methane is used as a raw material to obtain marketable and high value-added products, such as methanol. Methanol has a wide variety of applications such as used in the production of plastics or as a vehicular fuel, but there has been no domestic production since 2016. The direct conversion of methane to methanol is advantageous because methane is converted to methanol in a direct pathway without the formation of the intermediate synthesis gas that is obtained by conventional processes, thus reducing energy costs. Thus, this work aims to perform a techno-economic evaluation of the production of methanol from methane by direct catalytic partial oxidation. The simulation of the process of interest was performed in the process simulation software Aspen Plus V11©. The thermodynamic analysis of the partial oxidation process of methane with different oxidants was performed to verify the equilibrium of the reaction system and to evaluate the operational parameters that favor the conversion, the selectivity and the yield of the system. The preliminary economic analysis was based on calculations presented in the literature, to obtain the expected level of magnitude for the CAPEX, the magnitude level being a range of values in which the final CAPEX of the process lies. The production costs of methanol from the partial oxidation of methane for a production scale of 1500 tons/day of methanol in the isothermal process with O2 and CO2 for a conversion degree of 25% and yields of 75 and 80 µmol CH3OH/(g zeolite), respectively, resulted in an economically unfeasible process, where the operating costs (OPEX) were higher than the total sales value of the products. Assuming improved yields found experimentally (adopting 70% degree of conversion and with a yield of 360 µmol CH3OH/(g zeolite)) for the isothermal process with O2 resulted in a CAPEX and OPEX of US$27 million and US$5 million per year respectively, and payback of 5 years. For the isothermal process using carbon dioxide as oxidizing agent resulted in a CAPEX and OPEX of approximately, US$32 million and US$18 million per year respectively, and a payback of 6 years.